Efficiency of leadership development in teaching - Khadjayeva, Zh.B. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
Article discuses the topicality and efficiency of leadership development quality as one of the way of teachers for formation to their self-development and show it as effective method to involve students in educational process. Author analyses European and American program for teachers leadership developing and make conclusion that nowadays it isn’t enough just to be educators or teachers. Teacher has to be more aim-oriented, goal-seeking, far-sightedness, concerned. There are the abilities to look far into the future with regard to their company, class, team or department. Author considers that teachers need to have external and inner selfimprovement, assessing the society changes, environmental forces and competitor activities.
Оқытудағы көшбасшылықты дамытудың тиімділігі
Эффективность развития лидерства в преподавании
Keywords: teacher development; leadership; education system; self–development; teacher leadership development; leader; leadership development; teaching; educational activities